Advancing Africa's Soil Health Monitoring to Support the Nairobi Declaration and CAADP Kampala Agenda - African Union Development Agency, NEPAD (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This brief addresses the urgent need to improve soil health as a foundation for tackling Africa’s interconnected challenges of land degradation, climate change, food insecurity, and biodiversity loss. It aims to deepen technical understanding of key elements of soil health by promoting common definitions, robust monitoring systems, and relevant indicators. The brief supports African Union (AU) Member States in meeting their commitments under the Nairobi Declaration and the Comprehensive Africa Agriculture Development Programme (CAADP) Kampala Agenda, while contributing to the objectives of the African Fertilizer and Soil Health (AFSH) Action Plan and the new Ten-Year CAADP Strategy and Action Plan (2026-2035). It explores how soil health indicators can be effectively aligned with the current CAADP Biennial Review monitoring system and integrated into the CAADP Kampala framework by 2025. Through an examination of policy frameworks, indicator integration, and system design, the brief offers practical insights for advancing a coordinated and effective soil health monitoring agenda across the continent.